Hukum Tajam Ke Bawah Tumpul Ke Atas (Perspektif Sosiologis Penegakan Hukum di Indonesia) - Irwan, Irwan; Wira Perdana, Fadjrin; Lumban Tungkup, Doharman; Miran, Miran; Suteki, Suteki (Jurnal Indonesia Sosial Sains, 2022)
Weak law enforcement and equitable development as well as other discriminatory treatments still occur in the implementation of minority rights in Indonesia. The purpose of this research is to examine law enforcement "sharp down, blunt up" from a sociological legal perspective. This study uses a descriptive research method with a qualitative approach. Data collection was carried out by studying literature from previous studies, then used to analyze the phenomenon of legal decisions in Indonesia. The phenomenon of law sharp downwards and blunt upwards is the reality of law enforcement caused by legal practices that are oriented towards justice. Efforts to realize material (substantive) justice in law enforcement (criminal) in court, can be provided through a legal pluralism approach and the ability of judges to evaluate laws. Law enforcement must be carried out appropriately and effectively to measure the success of the state. The running Indonesian state of law must also pay attention to aspects of divinity, humanity, deliberation, and justice.